‘We have been in lockdown since he was born’: a mixed methods exploration of the experiences of families caring for children with intellectual disability during the COVID-19 pandemic in the UK - Diana Baralle; Susan Walker; Ramya Srinivasan; Sarah Davies; Shelagh Joss; Jonathan Berg; Miranda Splitt; Usha Kini; Pradeep Vasudevan; John Dean; William Newman; Yanick Crow; et al. (BMJ Open)
Objectives This study aimed to explore the experiences of parents caring for children with intellectual and developmental disabilities (IDD) during the UK national lockdown in spring 2020, resulting from the COVID-19 pandemic.Design Participants were identified using opportunity sampling from the IMAGINE-ID national (UK) cohort and completed an online survey followed by a semistructured interview. Interviews were analysed using thematic analysis.Setting Interviews were conducted over the telephone in July 2020 as the first UK lockdown was ending.Participants 23 mothers of children with intellectual and developmental disabilities aged 5–15 years were recruited.Results Themes reported by parents included: managing pre-existing challenges during a time of extreme change, having mixed emotions about the benefits and difficulties that arose during the lockdown and the need for appropriate, individualised support.Conclusions Our findings confirm observations previously found in UK parents of children with IDD and provide new insights on the use of technology during the pandemic for schooling and healthcare, as well as the need for regular check-ins.